2017
DOI: 10.3390/ijerph14121592
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate (Punica granatum) Juice Shows Antioxidant Activity against Cutaneous Leishmaniasis-Induced Oxidative Stress in Female BALB/c Mice

Abstract: Leishmania species are parasites that multiply within phagocytes and cause several clinical diseases characterized by single or multiple ulcerations. One of the complications that can induce tissue damage and the resulting scars is caused by secondary bacterial infections. Studies to find new, effective, and safe oral drugs for treating leishmaniasis are being conducted since several decades, owing to the problems associated with the use of antimonials available. Previously, the antiparasitic and antioxidant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…These results support the development of functional foods for the prevention obesity, diabetes and dyslipidemias [32]. Studies with mice models have demonstrated that pomegranate juice exhibits a protective effect against oxidative damage in Parkinson's disease as well as antileishmanial activity [33,34].…”
Section: Juice Composition and Health Propertiessupporting
confidence: 56%
“…These results support the development of functional foods for the prevention obesity, diabetes and dyslipidemias [32]. Studies with mice models have demonstrated that pomegranate juice exhibits a protective effect against oxidative damage in Parkinson's disease as well as antileishmanial activity [33,34].…”
Section: Juice Composition and Health Propertiessupporting
confidence: 56%
“…In the present study, we demonstrate that Ficus carica Linn (Fig) and Olea europaea (Olive) extracts with (Ag-NPs) improve skin lesions and promote their healing and parasite resolution in Balb/c mice infected with L. major, this activity may be attributed to the presence of phenolic and flavonoids compounds which possesses antileishmanial potency by enhancing non-specific immunity by macrophages activation and inducing NO, interferon-gamma and tumor necrosis factor-gamma, so those chemicals and cytokines produce fundamental host defense system and kill the invading parasite [47][48] (NFOA) treatment caused a significant reduction in the average lesion size and complete healing after 21 days compared to standard drug Pentostam that needs more than 28 days for healing. This is in accordance with previous reports [49][50][51][52][53]. Reactive oxygen species (ROS) formed during multiple normal processes in tissues and cells are involved in the pathogenesis of various parasitic infections including Leishmania spp., Toxoplasma gondii, Giardia lamblia, and Entameba histolytica [54][55][56][57].…”
Section: Discussionsupporting
confidence: 93%
“…Punica granatum juice treatment by oral administration significantly reduced the average size of cutaneous leishmaniasis lesions compared with that of untreated mice, and antileishmanial activity of P. granatum was associated with enhanced endogenous antioxidant enzyme activities. 40 Ethanol and hexane extracts of 16 Brazilian medicinal plants were tested against stationary-phase promastigotes of L. amazonensis. This in vitro assay showed six potent extracts, with IC 50 values varying from 0.08 to 44.10 μg mL -1 .…”
Section: Resultsmentioning
confidence: 99%